Revitalization of the Akidah Akhlak Curriculum in Madrasah Ibtidaiyah in the Era of Artificial Intelligence - Mutia Rahmawati; Syaifuddin Sabda (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to analyze the revitalization of the Akidah Akhlak curriculum at the Madrasah Ibtidaiyah level in the era of Artificial Intelligence through the integration of Islamic values, Islamic digital literacy, character education, and 21st-century competencies. This research employed a qualitative approach using library research methods by examining books, scientific journals, and relevant educational policy documents. Data were analyzed using content analysis techniques through data reduction, categorization, interpretation, and conclusion drawing. The findings indicate that the revitalization of the Akidah Akhlak curriculum needs to be carried out adaptively and transformatively by integrating critical thinking skills, digital ethics, communication, collaboration, creativity, and strengthening Islamic character values. In addition, the use of AI technology in moral learning can support interactive and contextual learning when accompanied by proper ethical guidance and supervision. The study concludes that the revitalization of the Akidah Akhlak curriculum in the AI era is essential to ensure the relevance of Islamic education, enabling students to develop strong moral character, digital responsibility, and 21st-century competencies while maintaining Islamic values as the foundation of learning